1996
DOI: 10.1162/jocn.1996.8.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Nonfluent Aphasia: Language, Cognitive, and PET Measures Contrasted with Probable Alzheimer's Disease

Abstract: The purpose of this study was to compare the language and cognitive profiles of four progressive nonfluent aphasia (PNFA) patients with 25 probable Alzheimer's disease (pAD) patients, and to identify the distinct cortical defects associated with cognitive deficits in PNFA using positron emission tomography (PET). Longitudinal observations of PNFA patients revealed progressively telegraphic speech and writing and a gradual deterioration of sentence comprehension, but memory and visual functioning were relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
152
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(164 citation statements)
references
References 73 publications
10
152
1
1
Order By: Relevance
“…It is also distinct from the production deficit typical of PNFA, in which articulation deficits and agrammatism predominate. 22 LPA patients, therefore, show a pattern of "intermediate" fluency distinct from the fluent SemDs and the nonfluent PNFAs, raising the issue of how to label their language production. Fluency is a composite measure, defined by multiple features of spontaneous language production.…”
Section: Verbal Response Pointingmentioning
confidence: 99%
“…It is also distinct from the production deficit typical of PNFA, in which articulation deficits and agrammatism predominate. 22 LPA patients, therefore, show a pattern of "intermediate" fluency distinct from the fluent SemDs and the nonfluent PNFAs, raising the issue of how to label their language production. Fluency is a composite measure, defined by multiple features of spontaneous language production.…”
Section: Verbal Response Pointingmentioning
confidence: 99%
“…Mesulam described primary progressive aphasia (PPA), with an isolated language deficit as the most prominent presenting feature, in the absence of strokes or tumors (Mesulam 1982(Mesulam , 1987(Mesulam , 2001. PPA has been divided into three syndromes (GornoTempini et al 2011): (1) Semantic dementia (SD), also known as semantic variant PPA, a fluent aphasia with loss of word meaning (Snowden et al 1989); (2) progressive nonfluent aphasia (PNFA), also known as nonfluent/ agrammatic variant PPA, a disorder characterized by effortful, nonfluent speech (Grossman et al 1996); and (3) logopenic progressive aphasia (LPA), also known as logopenic variant PPA, a nonfluent aphasia with deficits in word retrieval and sentence repetition (Gorno-Tempini et al 2004b).…”
Section: The Concept Of Frontotemporal Dementia: Historical Overviewmentioning
confidence: 99%
“…The grammatical processing deficit in PNFA appears to be related to left inferior frontal cortex: MRI studies of PNFA show gray matter atrophy in an inferior frontal distribution (Grossman & Ash, 2004;Nestor et al, 2003), and difficulty with sentence processing in PNFA has been linked to reduced activity in inferior frontal and anterior superior temporal portions of the left hemisphere using both PET (Grossman et al, 1996;Nestor et al, 2003) and SPECT . In an fMRI activation study of PNFA, we found reduced activation of ventral portions of left inferior frontal cortex during attempts to understand grammatically-challenging aspects of a sentence (Cooke et al, 2003).…”
Section: Sentence Processing In Pnfamentioning
confidence: 99%
“…PNFA is associated with atrophy to the left inferior frontal cortex and nearby regions such as anterior insula, dorsolateral prefrontal cortex, frontal operculum, and anterior superior temporal cortex (Gorno-Tempini et al, 2004;Grossman et al, 1996;Nestor et al, 2003). It is characterized by effortful and agrammatic speech which is often dysarthric and contains phonemic paraphasic errors (Grossman, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation